Animation Videos as a Pre-writing Stimulus: A Quasi-Experimental Study on Secondary School Students in Medan-Indonesia - Sinamo, Callista Buena; Astuti, Utari Praba; Ivone, Francisca Maria (Jurnal Pendidikan Progresif, 2024)
Abstract: Animation Videos as a Pre-writing Stimulus: A Quasi-Experimental Study on Secondary School Students in Medan-Indonesia. Objectives: This study aims to reassess the effectiveness of  animation videos as a stimulus during pre-writing phase on tenth graders’ writing skills. Methods: Employing a quasi-experimental research design, the study applied t-test and effect size analysis within a quantitative approach. Through non-random sampling, two intact classess of 30 tenth graders each were assigned to the control and experimental groups. Pre- and post-tests, focusing on the ability to write a procedure text in the tips genre, were conducted to collect data. Findings: The research findings indicated a significant difference in the writing scores of tenth graders who underwent process writing with animation videos during pre-writing, compared to those without such intervention. Particularly noteworthy were substantial differences observed in the organization aspect, while the least difference was noted in language aspect. Conclusion: This study suggests the essential role of  animation videos as a brainstorming stimulus in retrieving linguistic and topic knowledge for the students to effectively organize  and communicate  their ideas. Implications of these results for the involvement of animation videos during pre-writing in EFL settings are discussed. Keywords: EFL writing; secondary Indonesian students; writing skillsDOI: http://dx.doi.org/10.23960/jpp.v14.i1.202449